Malaria Frontline Project: strategic approaches to improve malaria control program leveraging experiences from Kano and Zamfara States, Nigeria, 2016-2019 - Adefisoye Adewole; Olufemi Ajumobi; Ndadilnasiya Waziri; Amina Abdullahi Umar; Usaini Bala; Saheed Gidado; Gideon Ugbenyo; Edwin Simple; Isaac Igbaver; Adam Attahiru; Charles A. Michael; Belinda Uba; et al. (BMC, 2023)
Abstract Background The Malaria Frontline Project (MFP) supported the National Malaria Elimination Program for effective program implementation in the high malaria-burden states of Kano and Zamfara adapting the National Stop Transmission of Polio (NSTOP) program elimination strategies. Project implementation The MFP was implemented in 34 LGAs in the two states (20 out of 44 in Kano and all 14 in Zamfara). MFP developed training materials and job aids tailored to expected service delivery for primary and district health facilities and strengthened supportive supervision. Pre- and post-implementation assessments of intervention impacts were conducted in both states. Results A total of 158 (Kano:83; Zamfara:75) and 180 (Kano:100; Zamfara:80) healthcare workers (HCWs), were interviewed for pre-and post-implementation assessments, respectively. The proportions of HCWs with correct knowledge on diagnostic criteria were Kano: 97.5% to 92.0% and Zamfara: 94.7% to 98.8%; and knowledge of recommended first line treatment of uncomplicated malaria were Kano: 68.7% to 76.0% and Zamfara: 69.3% to 65.0%. The proportion of HCWs who adhered to national guidelines for malaria diagnosis and treatment increased in both states (Kano: 36.1% to 73.0%; Zamfara: 39.2% to 67.5%) and HCW knowledge to confirm malaria diagnosis slightly decreased in Kano State but increased in Zamfara State (Kano: 97.5% to 92.0%; Zamfara: 94.8% to 98.8%). HCWs knowledge of correct IPTp drug increased in both states (Kano: 81.9% to 94.0%; Zamfara: 85.3% to 97.5%). Conclusion MFP was successfully implemented using tailored training materials, job aids, supportive supervision, and data use. The project strategy can likely be adapted to improve the effectiveness of malaria program implementation in other Nigerian states, and other malaria endemic countries.